Daily abundance at the breeding site and reproductive behavior of Polythore gigantea (Odonata: Polythoridae) (2014)
ABSTRACT : Daily abundance at the breeding site and reproductive behavior of Polythore gigantea (Selys, 1853) are described in different localities of Antioquia, Colombia. Observations were done between March and June 2009 from 08:00 to 16:00 h. The highest reproductive activity (i.e. maximal abundance of individuals at the breeding site) was observed between 11:06 and 12:12 h. Oviposition lasted 10 min on average. During courtship, the male exhibited rhythmical movements by opening and closing the wings rapidly, getting closer to the female and holding her in tandem. During oviposition, the female inserts the eggs inside wet trunks and little twigs in the surrounding vegetation under the close surveillance of the male. Males exhibit territorial behavior and conspecific aggression to defend the territory. Factors such as vegetation cover, might influence the time of the day in which oviposition occurs. This study provides, for the first time, information on the reproductive behavior of P. gigantea.